Applying UTAUT in a Governmental Environment: The Case of Young Saudi Public University - Naief G AZYABI (Communications of International Proceedings, 2021)
This paper aims to investigate the degree to which academics have accepted and use information systems. The study applied the Unified Theory of Acceptance and Use Technology (UTAUT) to understand the factors influencing acceptance and use of technology at a Young Saudi Public University (YSPU). A quantitative research approach was used and data collected through online surveys. The research instrument was developed based on four factors: performance expectancy, effort expectancy, influencing conditions, and social influence on behavior intentions towards an information system. The study findings showed a partial positive correlation between performance expectancy and information systems at the university. Furthermore, increased performance expectancy contributed to increased behavioral intentions in using Infosys. The findings further showed that effort expectancy had the largest impact on use intentions compared to the test of the variables under examination.
Keywords: UTAUT; Information Systems; IS Acceptance; UTAUT model